Sensory Quality and Cooking Loss of Broiler Chicken Nuggets with the Addition of Yellow Corn - Septian, I Gede Nano; Baeti, Husnul; Fahrullah, Fahrullah; Yulianto, Wahid; Kisworo, Djoko (CELEBES Agricultural, 2025)
The term "organoleptic testing" is synonymous with the more specific term "sensory evaluation". The objective of the study was to ascertain the impact of incorporating supplementary yellow corn in the formulation of broiler chicken nuggets on their sensory quality and cooking loss. The research method employed was of an experimental nature, utilising a Completely Randomised Design (CRD) with three distinct treatments: P0, representing the control, P1, which involved the incorporation of 25 g of yellow corn into a 100% nugget mixture (10%), P2, encompassing the addition of 37.5 g of yellow corn into a 100% nugget mixture (15%), and P3, comprising the inclusion of 50 g of yellow corn into a 100% nugget mixture (20%). Recent studies have demonstrated that the provision of yellow corn does not exert a significant influence on the sensory quality values and cooking losses of broiler chicken nuggets (p > 0.05). The cooking loss of P1 nuggets was found to be 0.019% lower than that of P2 nuggets (0.22%) and P3 nuggets (0.41%). The Duncan test demonstrated that there was a negligible difference between P1 and P2, and between P2 and P3. Furthermore, there was no significant difference between P2 and P3. The lowest cooking loss for chicken nuggets in the treatment with the addition of yellow corn was P1 0.019%. This shows that the higher the level of yellow corn added, the lower the cooking shrinkage. The lower the cooking shrinkage value, the better the product quality because there will be less nutritional loss, on the other hand, the higher the cooking shrinkage value, the lower the product quality. The findings showed that the provision of yellow corn did not have a significant effect on the sensory quality or cooking loss of broiler chicken nuggets.